Analysis of the yield of rosewood essential oil under experimental conditions - Chaves, André Luiz de Souza; Silva, Messe Elmer Torres; da Silva, Daniel; Sampaio, Paulo de Tarso Barbosa; Borges, Ryan Leão (Disciplinarum Scientia | Naturais e Tecnológicas, 2025)
Rosewood (Aniba roseodora Ducke), a species native to much of Latin America and once very common in Brazil, is widely used for the extraction of linalool. The high demand for its oil led to a disalignment between the extraction of its essential oil and the time taken for the natural regeneration of the species, almost leading to its extinction in the last century. In this context, the objective of this work was to develop a sustainable protocol for the extraction and yield of rosewood essential oil, from branches and leaves, on a laboratory scale. Three main variables that were correlated with each other were used: type of sample (branch or leaf), amount of water used in the hydrodistillation (1 L or 1.5 L) and extraction time (1 h, 1.5 h or 2 h). The data obtained were submitted to analysis of variance and, for comparison of the means of the treatments, the Tukey test was used at the level of 5% probability. We observed that there was a significant difference between the treatments tested. The treatment with 100 g of rosewood leaves when associated with 1 L of distilled water and submitted to 1 hour of extraction resulted in the highest average yield rate (0.70935 mL), in addition to an average linalool content that was greater among all the samples analyzed, being equal to 83.11% when compared with the other treatments. We conclude that the protocol developed on the extraction and yield of rosewood oil on a laboratory scale is efficient for the study in question; however, we suggest further studies for the optimization of the protocol in order to ensure the full sustainable development of this species of economic interest.